Títulos Valores y Derecho Mercantil - Zegarra Mulánovich, Álvaro (Revista de Derecho, 2019)
In this article two questions are met in connection with the systematics of the general theory of commercial papers or negotiable instruments. First, the question is considered of wether that theory pertains, as a general private Law doctrine, to the General Private Law (or “Derecho Civil”) or to the Commercial Law (“Derecho Mercantil”). Then the article deals with the problem of wether the same general theory of commercial papers is a part of Property Law or of the Contract Law. In both cases, the argumentation leads to a preference for the second alternative.